Studi Kapasitas Infiltrasi Metode Horton untuk Pemakaian Biopori di Kampus Universitas Bina Nusantara Berdasarkan Debit Limpasan Permukaan - Juliastuti, Juliastuti; Suhendra, Andryan (Bina Nusantara University, 2011)
Changes in land use due to the rapid growth of building construction leads to an increase in direct runoff, as well as declining water that seeped into the ground. Consequently, water distribution happens to be unequal of between the rainy and dry seasons. This phenomenon also occurs in the area of Kijang Campus - Bina Nusantara University which always comes up with puddles even though the rain falls with only a short duration. In this research the rainfall on the Kijang Campus - Bina Nusantara University is assessed based on the rainfall data record to obtain the rainfall intensity of various periods. Field survey is conducted to determine the existing infiltration capacity (with / without bio pore holes) and on-site. It is concluded based on the research results using Horton method that the soil on the Kijang Campus - Bina Nusantara University is earth embankment that has the infiltration capacity ranging between 0.0867 - 0.2165 m3/hr. This illustrates that the soil infiltration capacity is relatively small and thus requires the installation of bio pore holes with distance by 0.5 meters.